On the origin and behavior of irradiation-induced c-component dislocation loops in magnesium. (1st June 2017) - Xu, Weizong; Zhang, Yongfeng; Cheng, Guangming; Mathaudhu, Suveen N.; Scattergood, Ronald O.; Koch, Carl C.; Lavernia, Enrique J.; Zhu, Yuntian
Abstract: C-component dislocation loops are one of the unique defects in hexagonal close-packed (hcp) crystals that promote the accelerated growth and void formation under irradiation. Here, we report in situ observation of c-component dislocation loop formation in Mg under electron irradiation with emphasis on their atomic structures. Aberration-corrected scanning transmission electron microscopy imaging is utilized to reveal four possible types of double-layer loops, which were identified as different types of stacking fault and dislocation core structures. Triple- and quadruple-layer c-component dislocation loops were also observed. The formation mechanisms of the four types of double-layer loops were revealed via molecular dynamics simulations. The experimentally observed formation rate of the single- and double-layer dislocation loops is controlled by their formation energies. Our direct experimental observations in combination with molecular dynamics simulations provide fundamental insight into the mechanisms governing nucleation and growth of the c-component dislocation loops as well as their interactions, which could potentially help with future development of irradiation-resistant materials. Graphical abstract: Image 1